Memória social em Fortaleza: reflexões sobre Parangaba - Costa, Mario Sergio Barbosa (2011)
This work aims at understanding the processes of construction of social memory and interventions in the traditional urban neighborhood Parangaba, located in the southwest of Fortaleza. First, however, the author makes some considerations about the methodology employed in research work. After the historical reconstruction is performed in the neighborhood, addressing moments ranging from the ancient Indian village in the district today. Here, the focus of analysis is the social and collective memory of individuals and its relation to space and time. The next step was to build understanding of the processes represented by the memory of the old buildings of the site and the dilemmas or "conflicts" arising from the dichotomy upgrade / maintain. Finally, there is a brief analysis of urban interventions put into practice in place and some of the ambiguous character they play in redefining and uses of space, as well as important factors for the emergence of new social actors.